2010
DOI: 10.1242/dev.046896
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and propagation of enteric neural crest progenitor cells from mouse embryonic stem cells and embryos

Abstract: SUMMARYNeural crest is a source of diverse cell types, including the peripheral nervous system. The transcription factor Sox10 is expressed throughout early neural crest. We exploited Sox10 reporter and selection markers created by homologous recombination to investigate the generation, maintenance and expansion of neural crest progenitors. Sox10-GFP-positive cells are produced transiently from mouse embryonic stem (ES) cells by treatment with retinoic acid in combination with Fgf8b and the cytokine leukaemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 66 publications
3
44
0
Order By: Relevance
“…Recently, a combination of factors that promote self-renewal of these progenitors resulting in their significant expansion as undifferentiated NCCs was defined [76]. A Sox10-GFP transgene was used to isolate mESCs positive for GFP and these cells expressed NCC markers when cultured.…”
Section: Mouse and Human Esc-derived Neural Crest Stem Cellsmentioning
confidence: 99%
“…Recently, a combination of factors that promote self-renewal of these progenitors resulting in their significant expansion as undifferentiated NCCs was defined [76]. A Sox10-GFP transgene was used to isolate mESCs positive for GFP and these cells expressed NCC markers when cultured.…”
Section: Mouse and Human Esc-derived Neural Crest Stem Cellsmentioning
confidence: 99%
“…In this case, the Sox10-Venus-marked cells in Sox10-IRES-Venus mice should accurately reflect the behavior of the wildtype NC cells. Recently, chimeric mice generated from ES cells in which exon I of the Sox10 had been replaced by the GFP sequence were also reported to mark NC cells in vivo (Kawaguchi et al, 2010).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Although there are a number of possible sources of enteric neurons (4,5,7,8,10,11,13,16,(34)(35)(36)(37)(38)(39), enteric neural crest-derived ENS progenitors were chosen, as they are likely to be the most clinically relevant source of cells, are readily accessible (13), and can give rise to enteric neurons in the embryonic gut or when cocultured with colonic muscle from infants (13,14,18). We showed that after transplantation into the colon of postnatal mice, ENS progenitors proliferated; migrated extensively and differentiated into neurons with the neurochemical, morphological, and electrophysiological characteristics of enteric neurons; and received synaptic inputs.…”
Section: Introductionmentioning
confidence: 99%